Extending cytomegalovirus prophylaxis in high‐risk (D+/R−) lung transplant recipients from 6 to 9 months reduces cytomegalovirus disease: A retrospective study. Issue 4 (27th March 2020) - Herrera, Sabina; Khan, Basha; Singer, Lianne G.; Binnie, Matthew; Chaparro, Cecilia; Chow, Chung‐Wai; Martinu, Tereza; Tomlinson, George; Keshavjee, Shaf; Husain, Shahid; Tikkanen, Jussi M.
Abstract: Rationale: Cytomegalovirus (CMV)‐seronegative recipients receiving a seropositive allograft (D+/R−) are at a high risk of developing CMV disease. Our program increased the duration of CMV prophylaxis from 6 to 9 months in May 2013. Here, we present the impact on the incidence of CMV infection, disease, side effects, rejection, and other factors. Methods: Retrospective cohort of 241 CMV (D+/R−) patients transplanted between January 1, 2008, and December 31, 2017. Blood CMV testing was done according to protocol. All patients received ganciclovir/valganciclovir as prophylaxis. We compared the incidence and timing of CMV infection and disease up to 6 months after cessation of prophylaxis between patients who received 9 months (May 2013 onwards) and a historical control group who received 6 months of prophylaxis (prior to May 2013). CMV infection was defined as detectable CMV viremia in the absence of symptoms. CMV disease was defined as CMV syndrome or tissue‐invasive disease. Side effects of prophylaxis and CMV resistance were recorded. Results: A total of 116 patients were included in the 6‐month group and 125 in the 9‐month group. The extended 9‐month CMV prophylaxis delayed the onset of CMV infection (median time to CMV infection after lung transplantation 295 vs 353 days, P < .01) but did not significantly reduce the incidence of CMV infection (65% vs 64%, P = .06, log‐rank). The 9‐month prophylaxis delayed the onset and decreased the incidence of CMV disease from 50% in the 6‐month group to 42% ( P = .02 log‐rank). There was no difference in the rate of adverse effects (leukopenia in 32% in both groups, P = .53) or development of CMV resistance between the two groups (4 cases in both groups, P = .92). There were no significant differences in overall survival or the rate of chronic lung allograft dysfunction between the groups. Conclusions: Extending duration of CMV prophylaxis from 6 to 9 months resulted in a delayed and decreased incidence of CMV disease in our lung transplant population. The absolute risk reduction achieved by extended CMV prophylaxis was 8%. The incidence of CMV infection, and ganciclovir resistance and side effects were similar between the two groups. Our results suggest that extending CMV prophylaxis in the highest risk CMV D+/R− group is effective in reducing CMV disease.